Flocculation of kaolin from aqueous suspension using low dosages of acrylamide-based cationic flocculants - Suresha, P. R.; Badiger, Manohar V. (Journal of Applied Polymer Science, 2019)
Flocculation of kaolin from aqueous streams has become very important in view of its wide range of applications. In this work, cationic flocculants based on copolymers of acrylamide (AM) and 3-acrylamidopropyltrimethylammonium chloride (APTMAC) were synthesized with two different mole ratios of monomers, 80 mol % of AM (CP-8020) and 40 mol % of AM (CP-4060). The chemical structures of copolymers were confirmed by H-1 and carbon-13 nuclear magnetic resonance (C-13 NMR) spectroscopy. The molecular weight (MW) and zeta potential of the copolymers were determined. High MW was obtained for copolymer with high content of AM (CP-8020) and high zeta potential was observed for copolymer with high content of APTMAC (CP-4060). Flocculation of kaolin suspension was performed using both CP-8020 and CP-4060 and the flocculation was correlated to the zeta potential and MW of the copolymers. The optimum dosages of flocculants were determined. The mechanism of flocculation was discussed in terms of charge neutralization and bridging. The flocs of kaolin were characterized in terms of moisture content and size. To the best of our knowledge, this copolymer system was used for the first time for kaolin flocculation and found out to be efficient. (c) 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47286.
Keywords: copolymers; hydrophilic polymers; polyelectrolytes